(untitled) (Experimental biology, 2016)
On the basis of estimation of MDH-GOAT enzymatic complex activity Nadezhda variety is identified as highly tolerant to salinity, and Kazakhstanskaya 126 variety as susceptible. Phenotypic violation observed in stems and root system of Nadezhda and Kazakhstanskaya 126 varieties is associated with the action of 2% sodium chloride. Gene associated with Kazakhstanskaya 126 susceptibility to salinity is localized in chromosome 1B (9 μmol /ml), while high tolerance in Nadezhda variety is associated with genes localized in chromosomes 7B (290.4 μmol /ml), 6B (246.6 μmol /ml) and 3B (230.5 μmol/ml). The unique genetic material created on the basis of Kazakhstanskaya 126 variety in the form of monosomic lines series facilitates carrying out its genomic reconstruction, and same for the other perspective varieties of local selection originated from the highly tolerant to salinity Nadezhda variety.